Synergic Involvements of Microorganisms in the Biomedical Increase of Polyphenols and Flavonoids during the Fermentation of Ginger Juice - Christian Aimé Kayath; Armel Ibala Zamba; Saturnin Nicaise Mokémiabeka; Meddy Opa-Iloy; Paola Sandra Elenga Wilson; Moïse Doria Kaya-Ongoto; Rodd Jurah Mouellet Maboulou; Etienne Nguimbi (International Journal of Microbiology)
Steered fermentation by microorganisms gives great added value in the nutritional quality of local food. Ginger rhizome naturally contains a myriad of bioactive compounds including polyphenol and flavonoids. The aim of this work was to ferment the ginger juice, to evaluate the biochemical parameters of ginger wine, and to understand the involvement of microorganisms in the bioincrease of polyphenol compounds. Titratable acidity and pH values were determined and showed that pH is around 1.6 at the end of the fermentation when the acidity is around 6.431 g/L. Using colorimetric assay, the total polyphenolic and flavonoid compounds were evaluated throughout the fermentation. The variation of the polyphenol and flavonoid concentrations of the unsweetened sample was around 10.18 to 14.64 mg Eq AG/g and 1.394 to 2.224 mg Eq Cat/g Ms, but those from the sweet sample were around 10.82 to 18.34 mg Eq AG/g Ms and 1.311 to 2.290 mg Eq Cat/g. Using one-step PCR, multiplex techniques with specific primers, with yeast-like phenotype 27.27% (6), have been assigned among 22 isolates to Saccharomyces cerevisiae. By using PCR multiplex techniques, Bacillus licheniformis, Bacillus pumilus, Bacillus safensis, and Saccharomyces cerevisiae have been identified. Together with Saccharomyces cerevisiae, we showed that Bacillus sp. are able to secrete enzymatic landscape with some activities up to 50% including cellulase, amylase, pectinase, and protease.